Caso endoscópico - Pereira,Fernando (2011)
We present the case of an eight year-old girl with a family history of hammartous polyposis that was observed at the Pediatric Gastroenterology Department. Physical examination disclosed mucocutaneous melanic spots in the conjunctivae, lips, mouth and fingers, suggesting a Peutz-Jeghers syndrome and indicating an endoscopic screening. She performed a video capsule endoscopy that showed the presence of multiple polyps in the small bowel, supporting this diagnosis.